Vessel Operations in the Arctic, 2015–2017 - Silber, Gregory K.; Adams, Jeffrey D. (Frontiers in Marine Science, 2019)
The Arctic is among the most rapidly-changing regions on Earth. Diminishing levels of sea-ice has increased opportunities for maritime activities in historically inaccessible areas such as the Northern Sea Route and Northwest Passage. Degradation of Arctic marine ecosystems may accompany expanding vessel operations through introduced underwater noise, potential for large oil spills, among other things; and may compound stressors already effecting biological populations due to climate change. Assessments are needed to track changes in vessel traffic patterns and associated environmental impacts. We analyzed Arctic-wide vessel Automatic Identification System data 1 January 2015 to 31 December 2017 to quantify the amount and spatial distribution of vessel operations, assess possible changes in these operations, and establish a baseline for future monitoring. Nearly 400,000 vessel transits were analyzed. Number of trips, hours of operation, and amount of sea surface exposed to vessel traffic were used to compare operations between 14 delineated waterways. Operations were extensive and diverse: an average of 132,828 trips were made annually by over 5,000 different vessels. Transits were made in all areas studied and all months of the year. Maritime activities were intensive in some areas, but ice-limited in others. Amount of sea surface exposed to vessel traffic exceeded 70% in all but three areas. Bulk carriers, cargo ships, passenger/cruise ships, research survey ships, and vessels supporting oil/gas-related activities were represented. However, fishing vessels, primarily in the Barents, Bering, and Norwegian Seas, surpassed operations of all other vessel types and comprised about one-half of all voyages each year. We observed no overt increasing or decreasing trends in vessel traffic volume in our limited study period. Instead, inter-year variation was evident. While the number of unique vessels and transits increased year-to-year, hours of operation declined in the same period. Abundance/distribution of fisheries resources, economic feasibility of Arctic marine travel as weighed against inherent risks, and other factors likely accounted for inter-year variation in regional activity levels. Measures have been established to protect Arctic marine ecosystems but may need strengthening to address potential ecosystem threats from existing and growing commercial and industrial activities in the region.